Study on the use of Imazalil to continuous cropping obstacle of Ganoderma lucidum caused by Xylogone ganodermophthora - Qiuru Huang; Qi Lu; Fenghua Cao; Xiaomin Li; Xiaoping Wu; Huijuan Sun; Junli Zhang; Junsheng Fu (Chemical and Biological Technologies in Agriculture, 2024)
Abstract Background The Xylogone ganodermophthora is a pathogenic bacterium that poses a significant challenge to the continuous cultivation of the Ganoderma lucidum fungus. This study aims to identify and investigate specific agents for the effective prevention and control of X. ganodermophthora, establishing a theoretical foundation for overcoming this persistent challenge in G. lucidum cultivation. Results Using different G. lucidum soil as materials to study the presence of X. ganodermophthora in the soil. Additionally, the plate confrontation test was employed to investigate the impact of X. ganodermophthora on G. lucidum growth. The impact of physical factors and antibacterial agents on pathogenic bacteria was successfully carried out, with a further exploration of the effectiveness of field control. PCR amplification experiment and sequencing analysis verified that X. ganodermophthora existed in G. lucidum continuous cropping obstacle soil. This pathogenic bacteria has a significant inhibitory effect on the growth of G. lucidum, with an inhibition rate of up to 52.23%. High temperature, low temperature, light and other physical factors have no obvious inhibitory effect on this pathogen. Further investigation revealed that specific drugs, such as low concentrations (10 μL/mL) of Acticide DB20 and Imazalil, could effectively inhibit X. ganodermophthora growth in G. lucidum. Among them, Imazalil has a notable inhibitory effect on the growth of X. ganodermophthora. Conclusions Indoor toxicity test and field control results showed that Imazalil could effectively control the growth of pathogen X. ganodermophthora in G. lucidum continuous cropping obstacle, and promote the growth of G. lucidum. Graphical Abstract